[Obras de Emilio Ambasz] (A+U)
Se compilan obras del arquitecto y diseñador Emilio Ambasz. Contiene: Housing in an Agricultural Setting, Georgia, USA, 1977. Pro Memoria Garden between Memory and Amnesia, Lndenhausen near Hannover, West Germany, 1978. House for a Couple, Cordoba, Spain, 1978. Residence in a Ravine, Bierges near Brussels, Belginm, 1979. Graphic Design and Exhibition Design.